PROJECT AND REALIZATION OF WIFI NET - KOPRDA, Štefan; BREČKA, Peter; MAROŠ, Milan (Trends in education, 2009)
Actual expansion of ICT (in many ways much faster as human perception) forces us to adapt to the rate of its development. Mentioned development affects almost all areas of our existence and activities. It opens to us different kinds and possibilities of communication and as well as access to quantum of information. The computer net as such is being used for interaction and support of educational process.
Keywords: computer network; Wifi wireless network; routek.